2013
DOI: 10.3109/1354750x.2013.816778
|View full text |Cite
|
Sign up to set email alerts
|

Salivary alpha-amylase as a biomarker for the osmopressor response in healthy adults

Abstract: Water ingestion induces a sympathetically mediated increase in blood pressure in dysautonomic patients and the elderly, but not consistently in young healthy subjects. The aim of study was to determine the extent of the pressor response and changes of sympathetic activity biomarker salivary alpha-amylase (sAA) after water ingestion in young healthy subjects. Compared with ingestion of 50 mL of water, the blood pressure, total peripheral resistance and sAA significantly increased and the plasma osmolality decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The osmopressor response is similar in some respects to the 'diving reflex' in which trigeminal nerve stimulation by cold results in cardiac vagal activation and a profound bradycardia, as well as sympathetic activation and vasoconstriction [22]. The bradycardic response following water ingestion appears to have a slow increase in magnitude and a slow decay, a pattern more characteristic of a response have been thought to be driven by the stimulation of water's hypoosmolality [11,12].…”
Section: No Is One Of the Most Important Metabolic Modulators Of Bloodmentioning
confidence: 89%
See 1 more Smart Citation
“…The osmopressor response is similar in some respects to the 'diving reflex' in which trigeminal nerve stimulation by cold results in cardiac vagal activation and a profound bradycardia, as well as sympathetic activation and vasoconstriction [22]. The bradycardic response following water ingestion appears to have a slow increase in magnitude and a slow decay, a pattern more characteristic of a response have been thought to be driven by the stimulation of water's hypoosmolality [11,12].…”
Section: No Is One Of the Most Important Metabolic Modulators Of Bloodmentioning
confidence: 89%
“…An antecubital venous catheter was inserted for blood sampling at least 15 min before the beginning of the test, with the patient in the sitting position. Hemodynamic parameters including heart rate (HR), BP, stroke volume (SV), cardiac index (CI), and total peripheral vascular resistance (TPR) were measured using a Finometer (FMS, Finapres Measurement Systems, Arnhem, The Netherlands) [10][11][12]. Computation of stroke volume and cardiac output using the Model flow method was based on the finger arterial pressure [13].…”
Section: Instrumentationmentioning
confidence: 99%
“…Past research indicates that the haemodynamic response to water ingestion is independent of changes in plasma renin activity, vasopressin or blood volume [ 2 ] and there is compelling evidence that it is secondary to the activation of the transient receptor potential cation channel family (TRPV4 osmolarity-sensitive Ca 2+ channels) within the hepatic spinal afferents, dorsal root ganglia and spinal cord [ 28 ]. More recently, it was also shown that the osmopressor effect occurs simultaneously with the up-regulation of aquaporin-1 tyrosine phosphorylation on red blood cells [ 5 ]. This is important because the sympathetic nervous system is a major target of osmoregulatory neural pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Even though men exhibited higher BMI than women, the clinical relevance of this is questionable because the mean values of both groups was between normal values (i.e. 18.5 and 24.9 kg/m 2 ) [- 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation